(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2018)
Under mountain and steppe conditions of the Almaty Region, morphogenetic traits of almost 40 cultivars of common bean, Phaseolus vulgaris L. from Kazakhstan as well as American, Chinese, Polish, Russian, Turkish, and Czech collections have been assessed. Six local and foreign accessions have been subject to high-performance liquid chromatography to identify amino acid composition. Studied accessions, varieties and lines could be classified by an Osborne classification presenting bulk of proteins. Ketogenic amino acids (leucine, lysine and tryptophan) have been detected in much lower concentrations thus allowing to recommend related cultivars and lines for manufacturing diabetic products with a minor risk of ketone bodies accumulation. Essential amino acids have been registered to achieve 27.5-29.8%. Local lines have been determined to contain the greatest amount of sulfur-containing amino acids, methionine and cysteine (335-350 mg / 100 g and 55-62 mg/100 g, respectively). In addition, the line “Aktatti” has appeared to be enriched by lysine (410 mg/100 g). Accumulation of sulfur-containing amino acids may point to slowing down seed protein storage under sharply continental conditions. It is thereby confirmed that the protein content is dependent of the climatic changes, breeding technologies, soil characteristics and genotypic classification of the variety or line.